Injil Yohanes :Kristologi dan Iman Jemaat Perdana (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study aims to explore Christology in the Gospel of John, specifically the identity of Jesus as the pre-existent Word (Logos), His incarnation, the claim to divinity through the statement "ego eimi," unity with the Father, and its relevance for the early church and the contemporary church. The method used is a qualitative approach through literature study, with the primary source being the Gospel of John (especially John 1:1-18 and the statement "ego eimi"), supported by commentaries, theological journals, and the works of scholars such as Culpepper, Bauckham, and Dunn, analyzed in historical and theological contexts. The results show that John presents an explicit high Christology, depicting Jesus as the true God who became man, with theological essences such as the basis of worship, the certainty of salvation, and the resilience of faith for the congregation facing exclusion and polemics, while also being relevant for the foundation of faith, pastoral comfort, and missionary motivation in the current era of pluralism.